Analisis Manajemen Risiko Pada UMKM “ JIBALSTONES “ Jalan Pasir Impun Bandung - Mustofa, Rizal; Yunnawirudin Haq, Fajar; Satria Dimas, Muhammad (Jurnal Serambi Ekonomi dan Bisnis, 2024)
Risk management is an important step for Micro, Small, and Medium Enterprises (MSMEs) in the natural stone industry to ensure business sustainability and stability. This study aims to identify and analyze the main risks faced by natural stone MSMEs, as well as design effective mitigation strategies. The methods used include qualitative analysis based on interviews with MSME actors and related literature reviews. The results of the study show that the main risks include fluctuations in raw material prices, dependence on manual labor, incompatibility of orders with production results, and the impact of changes in government policies. To overcome these risks, it is recommended to implement supplier diversification, labor training, digitalization of production processes, and understanding the latest regulations. This study makes a practical contribution for natural stone MSME managers to increase the competitiveness and resilience of their businesses to risks